Implementation of Education Policy to Support Vision and Mission at MIS Ummul Quraa Tembung, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra Province - Tengku Darmansyah; Akbar Rafsanjani; Khoirun Nisa; Salwa Nabila Damanik (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
In preparing policies relating to education in In Indonesia, education tends to be interpreted as a conscious effort to help develop the personality and abilities of students. Management unprofessional madrasahs can hinder the progress of the madrasah To carry out its function as a formal educational institution, a plan is needed strategic as an effort or way to control the school effectively effective and efficient. The components in strategic planning consist of at least: of the vision, mission, goals, objectives and strategies must be carried out by the manager madrasas, so that madrasas have a policy direction that can support them achieving the expected goals. This research aims to describe education policy to support the vision and mission of the Ummul Quraa private Madrasah Ibtidaiyah. The method used in the research is qualitative descriptive. The research design used is a case study with observing policies at the private Ummul Quraa Madrasah Ibtidaiyah This research uses observation, interview and data collection techniques documentation. The party participating in this research was the chairman of the foundation and the head of the private Ibtidaiyah madrasah Ummul Quraa. That policy is the goal to improve raw materials, namely teachers, students and also facilities the infrastructure. Application of vision and mission.